ENVIRONMENTAL INTERPRETATION AND NATURE WALKS: THE USE OF THE FOLDER/PORTFOLIO AS AN EDUCATIONAL TOOL - Kiefer, Ana Paula; Von Ahn, Maurício Mendes; Redin, Ezequiel; Figueiró, Adriano Severo (Geosaberes, 2025)
Environmental interpretation has, over the past few years, become established as an educational tool used in numerous activities, providing knowledge generation in an accessible language. From this perspective, the objective of this text is to analyze the effectiveness of the interpretive brochure, developed and made available to participants of the Nature Walk held in December 2024 in Silveira Martins, as a way to aid in understanding the historical, cultural, and landscape elements of the route. The methodology adopted is based on the hypothetical-deductive method, assuming that the brochure will contribute to the walkers' experience. The research involved a theoretical review, the creation and layout of the brochure, and the application of a questionnaire with 12 objective questions to 100 participants, of whom only 35 responded. The results indicate that the use of the brochure is an effective tool for the dynamics of the walks and that it can be replicated for future editions. The brochure is considered effective in promoting environmental interpretation because it sparks curiosity and facilitates understanding of the route as a place of historical, cultural, and scenic importance in the municipality of Silveira Martins.